Bacterial Community Legacy Effects Following the Agia Zoni II Oil-Spill, Greece - Thomas, Gareth E.; Cameron, Tom C.; Campo, Pablo; Clark, Dave R.; Coulon, Frederic; Gregson, Benjamin H.; Hepburn, Leanne J.; McGenity, Terry J.; Miliou, Anastasia; Whitby, Corinne; McKew, Boyd A. (Frontiers in Microbiology, 2020)
In September 2017 the Agia Zoni II sank in the Saronic Gulf, Greece, releasing approximately 500 tonnes of heavy fuel oil, contaminating the Salamina and Athens coastlines. Effects of the spill, and remediation efforts, on sediment microbial communities were quantified over the following seven months. Five days post-spill, the concentration of measured hydrocarbons within surface sediments of contaminated beaches was 1,093-3,773 µg g-1 dry sediment (91% alkanes and 9% polycyclic aromatic hydrocarbons), but measured hydrocarbons decreased rapidly after extensive clean-up operations. Bacterial genera known to contain oil-degrading species increased in abundance, including Alcanivorax, Cycloclasticus, Oleibacter, Oleiphilus, and Thalassolituus, and the species Marinobacter hydrocarbonoclasticus from approximately 0.02% to >32% (collectively) of the total bacterial community. Abundance of genera with known hydrocarbon-degraders then decreased one month after clean-up. However, a legacy effect was observed within the bacterial community, whereby Alcanivorax and Cycloclasticus persisted for several months after the oil spill in formerly contaminated sites. This study is the first to evaluate the effect of the Agia Zoni II oil-spill on microbial communities in an oligotrophic sea, where in-situ oil-spill studies are rare. The results aid the advancement of post-spill monitoring models, which can predict the capability of environments to naturally attenuate oil.